Infrared Thermal Signature Evaluation of a Pure and Saline Ice for Marine Operations in Cold Climate - Rashid, Taimur; Khawaja, Hassan Abbas; Edvardsen, Kåre; Mughal, Umair Najeeb (International Frequency Sensors Association, 2015)
Marine operations in cold climates are subjected to abundant ice accretion, which can lead to heavy ice loads over larger surface area. For safe and adequate operations on marine vessels over a larger area, remote ice detection and ice mitigation system can be useful. To study this remote ice detection option, lab experimentation was performed to detect the thermal gradient of ice with the infrared camera. Two different samples of ice blocks were prepared from tap water and saline water collected from the North Atlantic Ocean stream. The surfaces of ice samples were observed at room temperature. A complete thermal signature over the surface area was detected and recorded until the meltdown process was completed. Different temperature profiles for saline and pure ice samples were observed, which were kept under similar conditions. This article is focused to understand the experimentation methodology and thermal signatures of samples. However, challenges remains in terms of the validation of the detection signature and elimination of false detection.